Coping strategies and family support to the adjustment of adolescents who have parents working as migrant workers - Rachmawati, Praba Diyan; Fitryasari P. K., Rizki; Pramesti, Dewita; Thomas, Deena Clare; Arief, Yuni Sufyanti (Universitas Airlangga, 2023)
Introduction: Adolescents often have difficulty adjusting to their surroundings. Coping and family support are also associated with this adjustment. However, the relationship between the aforementioned factors and adjustment among adolescents with parents who work as migrant workers remains unclear. This study aimed to analyze the relationship between coping and family support with the adjustment of adolescents who have parents who work as migrant workers. Methods: This is a cross-sectional study. A total of 70 early adolescents with parents working as migrant workers were recruited from the total sample. In this study, coping strategies and family social support were assigned as independent variables, while the dependent variable was the adjustment of adolescents who had parents as migrant workers. The questionnaire was used to measure the outcome of interest and tested for validity and reliability. The data analysis in this study used Spearman Rho. Spearman's Rho correlation with alpha, α set â‰¤ 0.05, was used to analyze the data. Results: The results indicate that Coping strategies (p = 0.018; r = 0.283) and family support (p = 0.001; r = 0.380) were associated with adolescent adjustment. Conclusions: Both coping strategies and family support contribute to the adjustment of adolescents whose parents work as migrant workers. There is a need to increase the priority of psychosocial counseling for adolescents who have parents working as migrant workers and educate their families to increase attention and support appropriate adolescent development.